[MS] Analisis Keperluan Ibu Bapa Terhadap Pembelajaran Kelas al-Quran dan Fardu Ain (KAFA) Secara Pendekatan Homeschooling untuk Murid Sekolah Rendah: The Needs Analysis of Parents for Learning al-Quran and Fardu Ain (KAFA) Classes through Homeschooling for Primary School Students (Afaq Lughawiyyah, 2024)
The implementation of al-Quran and Fardu Ain (KAFA) class learning for three decades has shown various flaws and problems, especially from the aspect of teaching and learning effectiveness (PdP) in the classroom. Among them are aspects of the implementation of teachers' teaching strategies and methods, the use of teaching aids, the use of resources based on information and communication technology (ICT), as well as teacher professionalism. This study intends to identify the needs analysis of parents for learning KAFA classes through homeschooling method for primary school students. Needs analysis is examined on three aspects, as follows: (i) perception of parents towards KAFA; (ii) student’s ability in KAFA’s subjects and (iii) the needs of homeschooling for KAFA class. Data collection was done through a quantitative design with a sampling of 86 parents. A list of five-point Likert questionnaires was provided for data collection according to the needs analysis aspects. The data obtained was analyzed through the computer software Statistical Package for the Social Sciences (SPSS) version 29.0.1.0 to see the mean and percentage of the study. Data findings suggest on (i) parents' perception were at a high level towards KAFA class (M=4.27, SD=0.57), (ii) students’ ability in KAFA’s subjects were also at a high level (M=4.06, SD=0.58), and (iii) parents showed a moderately high tendency towards the needs of homeschooling for KAFA class (M=3.40, SD=0.74). The main purpose of this study is to be able to provide preliminary information about the need to provide a homeschooling model of al-Quran and Fardu Ain (KAFA) classes for primary school students.